PENGARUH LIKUIDITAS, PROFITABILITAS, DAN SOLVABILITAS TERHADAP HARGA SAHAM PERUSAHAAN (Studi Kasus Pada Perusahaan Minyak Sawit (CPO) Yang Terdaftar Di Bursa Efek Indonesia) - Fiddah Faridah (Program Studi Manajemen Fakultas Ekonomi UST, 2023)
The purpose of this research is to investigate how palm oil companies' liquidity, profitability, and solvency affect stock prices from 2019 to 2021. Current Ratio, Return on Assets, and Debt to Equity Ratio are the analyzed financial ratios, with stock prices serving as the dependent variable. The research tool used in this study is an Eviews trial, and the research method used in this study is panel data regression analysis. The data used in this study are secondary data. This study's population and sample were ten IDX-listed palm oil companies. Partially, the findings demonstrated that the Indonesia Stock Exchange (IDX) share prices of palm oil companies were unaffected by the Current Ratio and Debt to Equity Ratio variables. The Indonesia Stock Exchange (IDX) stock prices of palm oil companies are influenced in part by the Return On Assets variable. Stock prices are unaffected by the Current Ratio, Return on Assets, and Debt to Equity Ratio simultaneously. As a result, the researchers hope that it can be taken into account when setting company policies regarding financial developments.